CONSTITUTIONAL COURT AS AN AUTHORITY FOR DISPUTE RESOLUTION - A. Polovchenko, Konstantin; P. Arak, Leonid (Gênero & Direito, 2020)
The article presents an analysis of the powers of the Republic of Serbia Constitutional Court to resolve competency and electoral disputes. The leading method in this study is the system analysis, which allows a comprehensive review of the system of measures and procedures aimed at implementing the dispute resolution function of the constitutional justice body of Serbia. Analyzing the evolution of the organizational process and the expansion of the practice of Serbian Constitutional Court, the author concluded that the modern constitutional legislation of the Republic of Serbia provided the judicial constitutional control body with sufficiently effective capabilities to resolve a wide range of legal disputes to protect the principles of the rule of law, constitutionality, legitimacy, and separation of powers, as well as rights to regional autonomy and local governance.